Ocular surface changes in allergic blepharoconjunctivitis and dry eye syndrome: diagnosis and therapy possibilities - S. N. Sakhnov; S. V. Yanchenko; A. V. Malyshev; Sh. J. Teshaev; M. Yu. Odilov; G. R. Odilova (Российский офтальмологический журнал)
Purpose: to evaluate the ocular surface changes (OSC) in seasonal and chronic allergic blepharoconjunctivitis (ABC) under dry eye (DE) conditions and to consider therapeutic possibilities.Materials and methods. 60 patients with seasonal ABC and mild DE syndrome (group 1) and 50 patients with chronic ABC and moderate DE syndrome (group 2) were tested for lipid deficiency (LD; negative lipid-interference test), aqua-deficiency (AD; inferior tear meniscus height < 250 ﬁm), and mucose deficiency (Bijsterveld`s xerosis index > 3 scores; XI, scores), Ocular surface disease index (OSDI), tear film break-up time (TBUT, seconds), meibomian gland dysfunction (MGD) according to Korb, taking into account the proportion of MGD (%) and its severity (MGDS, scores), and the “lid-wiper” symptom (LWS, scores) Statistics: M ± s; Mann — Whitney U-test; differences were statistically significant at p < 0.05.Results. LD was diagnosed in 65% of the 1st group patients (OSDI 32.3 ± 4.2, TBUT 6.5 ± 0.6, TMH 363.4 ± 43.96, XI 2.1 ± 0.4, MGDproportion — 41.02 %, LWS 1.1 ± 0.2). LD and MD were detected in 35 % of 1st group patients (OSDI 41.3 ± 5.7, TBUT 5.7 ± 0.5, TMH 332.9 ± 29.9, XI 4.2 ± 0.7, MGD proportion — 61.9 %, LWS 1.24 ± 0.4). The differences in OSDI, TBUT and XI values between DE patients with LD and DE patients with LD and MD were statistically significant. LD and AD were diagnosed in 48 % of 2nd group (OSDI 48.5 ± 6.4, TBUT 5.5 ± 0.6, TMH 192.3 ± 20.8, XI 2.5 ± 0.5, MGDS 1.8 ± 0.4, LWS 1.9 ± 0.3). LD, AD and MD were detected in 52 % of the 2nd group patients (OSDI 57.5 ± 5.8, TBUT 4.6 ± 0.6, TMH 177.7 ± 16.9, XI 5.5 ± 0.6, MGD-S 2.2 ± 0.4, LWS 2.3 ± 0.4). The differences in OSDI, TBUT and XI values between DE patients with LD-AD combination and DE patients with LD-AD-MD were statistically significant.Conclusion. OSC included lipid deficiency (65 %) and lipid-mucose deficiency (35 %) in S-ABC patients; OSC were represented by lipid-aqua-deficiency (48 %) and lipid-aqua-mucose-deficiency (52 %) in C-ABC patients. In our opinion, the diagnostics of these clinical variants of OSP diagnosis, opens up opportunities for differentiated tear replacement therapy. MGD was diagnosed in one half of S-ABC patients and in all C-ABC patients, which we believe determines another possible therapy direction — eyelid therapeutic hygiene aimed at MGD relieving and lipid deficiency compensation.